THE EFFECT OF SERVICE QUALITY AND PRICE ON CONSUMER PURCHASE DECISIONS THROUGH PURCHASE INTEREST ON ONLINE SHOPEE SHOPPING SITES - Rico Jaherman; Wagiarto Hoesin; Iwan Kurniawan (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to: 1) Analyze the effect of service quality and price on consumer buying interest, 2) Analyze the effect of service quality and price on consumer purchasing decisions, 3) Analyze the effect of buying interest on consumer purchasing decisions, 4) Analyze the effect of service quality and price on purchasing decisions through buying interest. This research was conducted on customers of the Shopee online shopping site which is managed by PT. Shopee Indonesia. The sampling technique used a random technique with analytical methods using descriptive analysis methods and path analysis. The results show that: 1) there is an influence of service quality and price on buying interest, 2) there is an influence of service quality and price on purchasing decisions, 3) there is an influence of buying interest on purchasing decisions, 4) buying interest cannot mediate to increase the effect of quality services and prices on consumer purchasing decisions on the Shopee online shopping site managed by PT. Shopee Indonesia